Antibacterial and photocatalytic activities of biosynthesized zinc oxide nanoparticle using novel plant P. macrosolen L. leaf extract - Abel Saka Gungure; Leta Tesfaye Jule; N. Nagaprasad; Krishnaraj Ramaswamy; Shanmugam Ramaswamy (Discover Materials)
Abstract In this study, ZnO nanoparticles were produced by an easy and cost effective approach using P. macrosolen L. leaf extract and zinc chloride as Zn ion source. The as-biosynthesized ZnO nanoparticles were analyzed by powder-X-ray diffraction (PXRD), Fourier transform infrared (FTIR) spectroscopy, UV–visible spectroscopy, Focused ion beam-scanning electron microscopy (FIB-SEM) and energy dispersive X-ray (EDX) characterization techniques. The XRD result revealed the formations of ZnO-nanoparticles with hexagonal structure, spherical like shape and average crystalline size of 47 nm. The presence of flavonoids in P. macrosolen L. extracts was confirmed by phytochemical tests, indicating that flavonoids primarily acted as reducing agents during nanoparticle formation. The FTIR spectrum also revealed broad and strong peaks corresponding to –OH groups, confirming the high concentration of phenolic acids present in the extract. The energy band gap of the biosynthesized ZnO Nanoparticles, calculated using the Tauc relation, was found to be 3.0 eV, indicating the presence of a blue shift. FIB-SEM was used to analyze the microstructure and identify any aggregations. The EDX analysis revealed the presence of zinc and oxygen, with weights of 16.33% and 83.67%, respectively. The disk diffusion test was performed on solid agar plates and demonstrated that the substance is effective against E. coli bacteria as an antibacterial agent. The photocatalytic degradation rate constants of the optimized ZnO samples under visible light are approximately 0.06455 min⁻1 for MO and 0.04865 min⁻1 for TB, achieving 94.47% and 92.34% degradation of MO and TB, respectively. These rates are significantly higher compared to unmodified ZnO, which has a degradation rate of 0.0075 min⁻1. The improvement in visible-light photocatalytic performance can be attributed to the formation of ZnO nanoparticles, which arise from the matching of crystal lattices and energy bands in ZnO. ZnO Nanoparticles produce excited electrons under visible light irradiation. These excited electrons in the ZnO nanoparticles are directly transferred to the conduction band (CB), resulting in notable visible light photocatalytic performance.